Evaluasi Penggunaan Tepung Daun Cengkeh (Syzygium aromaticum) terhadap Kualitas Fisik Jagung Pecah setelah Penyimpanan - Harun Kondoa; Lily Joris; Shirley Fredriksz (Jambura Journal of Animal Science, 2023)
The purpose of this research is to find out about the evaluation of using clove leaves powder with different percentages on the physical quality of corngrit that is being stored for two months. This research is done in the Feed Technology and Engineering Laboratory of the animal husbandry department, Faculty of Agriculture, Pattimura University in the period of September to November 2022. This research consists of 4 treatments and 4 repetition, P0 = 1500g corn grit  + 0g clove leaves powder (0%); P1 = 1500g corn grit + 225g clove leaves powder (15%); P2 = 1500g corn grit  + 450g clove leaves powder (30%); P3 = 1500g corn grit  + 675g clove leaves powder (45%). The variables that are being observed in this research include weight, color, smell, lice, and fungus. The result of the research shows that the addition of 30% and 45% clove leaves powder in 1500g of corn grit  gives better results to the physical quality of grit because they suppress lice infestation and fungus growth. The treatments also give distinct fragrant clove leaves, instead of the usual musty odor that appears on the corn grit that has been stored for 2 months.